The Influence of Gratitude on Psychological Resilience of Adolescence Living in Youth Social Care Institutions - Ratih Arruum Listiyandini (Journal of Educational, Health and Community Psychology, 2018)
This study aims to determine the role of gratitude on psychological resilience of adolescents who live in youth social care institutions (orphanages). The study was conducted using a quantitative cross-sectional design. The population of the study was adolescents who lived at youth social care institutions in Jakarta and Bekasi. Two hundred samples were obtained by convenience sampling. The researcher used the Indonesian version of gratitude scale and an adapted resilience scale as measurement tools. Regression analysis found that gratitude explains 13.1 percent variance of adolescences’ psychological resilience. The role of gratitude toward psychological resilience is positive, indicating that higher gratitude reflect higher resilience. Therefore, gratitude needs to be considered in the development of resilience program for adolescents living in youth social care institutions. Keywords: adolescence, gratitude, orphanages, resilience, social care.